A new technique of revision septoplasty using semi-penetrating straight and circular incisions of the nasal septum. Issue 6 (30th May 2019) - Wei, L; Wang, L; Lu, W; Jiang, T; Liu, Z; Wang, M; Wu, X; Wang, Z
Abstract: Objective: This study aimed to investigate endoscopic revision septoplasty with semi-penetrating straight and circular incisions in patients for whom septoplasty was unsuccessful. Method: Patients in this study ( n = 14) had a deviation of the nasal septum after septoplasty. Pre-operative and post-operative assessments were performed using a visual analogue scale and nasal endoscope. Semi-penetrating straight and circular incisions in front of the caudal septum and at the margin of the nasal septal cartilage–bone defect, respectively, were made. The mucoperichondrium and mucoperiosteum were bilaterally dissected until interlinkage with the cartilage–bone defect was achieved. Mucous membranes within the circular incision as well as the right mucoperichondrium and mucoperiosteal flaps were protected by pushing them to the right. This exposed the osteocartilaginous framework and allowed correction of the residual deviation. The patients were followed up for 30–71 months. Results: For nasal obstruction and headaches, a significant improvement was noted in post-operative compared to pre-operative visual analogue scale scores. No patients had septal deviations, saddle nose, false hump nose or contracture of the nasal columella. Conclusion: The technique allowed exposure of the septal osteocartilaginous framework and a broad operational vision, which enabled successful correction of various deformities of the nasal septum.